El cáncer de próstata en la actualidad - Pascual, Carolina; García, José Ángel; Fernández, Belén (Psicooncología, 2004)
In Spain, prostate cancer is the third cause of death among men. However, nowadays many patients are diagnosed in initial stages of the disease, which increases treatment possibilities. This raises the number of men that live many years being diagnosed and treated for this disease, reason why the influence that treatment indirect effects, fundamentally urinary incontinence and sexual impotence, have in quality of life has become specially important. In the present work, after reviewing the available bibliography, we have made an analysis of prostate cancer patients situation related to their adaptation to disease and psycho-social needs.